25(OH) Vitamin D is Associated with Greater Muscle Strength in Healthy Men and Women - Grimaldi, Adam S. (2013)
PURPOSE: The purpose of the study was to examine the relationship between serum 25-hydroxy vitamin D (25(OH)D) levels and muscle strength in 419 healthy men and women over a broad age range (20-76 years of age). METHODS: Isometric and isokinetic strength of the arms and legs was measured using computerized dynamometry and its relation to vitamin D was tested in multivariate models controlling for age, gender, resting heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), body mass index (BMI), maximal oxygen uptake (VO(2max),), physical activity counts, and season of vitamin D measurement. RESULTS: Vitamin D was significantly associated with arm and leg muscle strength when controlling for age and gender. When controlling for other covariates listed above, vitamin D remained directly related to both isometric and isokinetic arm strength but only to isometric leg strength. CONCLUSION: These data suggests that there may be a differential effect of vitamin D on upper and lower body strength. The mechanism for this difference remains unclear but could be related to differences in androgenic effects or to differences in vitamin D receptor expression. Our study supports a direct relationship between vitamin D and muscle strength and suggests that vitamin D supplementation be evaluated to determine if it is an effective therapy to preserve muscle strength in adults.